Classic Learning Media Such As Image Media: Do They Still Have An Impact On Learning In Elementary Schools? - Rizki Ananda; Pratama, Farhan Fajar (International Journal of Education and Teaching Zone, 2024)
This research aims to determine the impact of classical image media in improving student learning outcomes in science subjects amidst developments in time and technology. This research is classroom action research carried out at MI No. 34/E-3 Bunga Tanjung. The subjects in this research used purposive sampling, namely with the researcher's consideration that there were 20 students studying science material. The data collection technique in this research used a descriptive test sheet with a total of 5 questions, as well as a student and teacher activity questionnaire sheet as well as random student interviews (10 students), which were used as supporting data for the research results. The data analysis technique used is by assessing the average test results of students' scores with a minimum completion criteria indicator (KKM) = 70, where students will be said to be successful if their average score is the same or more than the KKM score, and also the research will be considered successful if 75% of students passed. The results of the research carried out in the first cycle showed that out of 20 students, they got an average score of 63, where only seven students were successful, or around 35%, while 13 students, or 65%, still had not succeeded in fulfilling the KKM so they were still must be continued in cycle II. The results of the research in the second cycle showed an increase where out of 20 students, they got an average score of 82, where 17 students, or 85%, succeeded in fulfilling the KKM, and only three students, or around 15%, had not yet met the KKM, so they had more than 75% of students were declared successful, and it could be concluded that the research was successful and did not need to be continued in cycle III.